Analysis of Reason Bayani, Burhani, and 'Irfani's in Islamic Studies - Aqiel Mutawalli; Muhammad Irsawandi; M. Rizky Bahar Siregar; Mohammad Al Farabi; Zulkifli Tanjung (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper analyzes the ideas of one of the foremost Arab thinkers, Muhammad Abed al-Jabiri. As a leading Moroccan Muslim thinker, Al-Jâbirî offers three approaches (bayânî, burhânî, and 'irfânî) to Islamic studies. This paper aims to provide an understanding of the three approaches. The type of research used is library research. The results showed that; 1) Bayani reason places text (revelation) as an absolute truth, 2) knowledge is obtained by conscience, where with a pure heart, it is hoped that God will bestow knowledge directly to Him, 3) Burhani upholds intellectual abilities in the form of senses, experience, reason and ratio in an effort to achieve and prove this knowledge and truth.